Islamic Perspective on Understanding Financial Management of Rural Households - Eli Rahmayati Pohan; Rahma Sartika Pasaribu; Fajar Trianida; Marlya Fatira AK; Selfi Afriani Gultom (Universitas Serambi Mekkah, 2024)
Knowledge about financial and budget management is not only an activity that is only carried out in industrial companies, trade or the like, but has made it mandatory for all households to be able to do it, because it is necessary to realize that a home includes a husband, wife and children. is a small corporate unit. No, family size and number of dependents hurt financial satisfaction in the family. Financial management knowledge in the form of planning, organizing, implementing, and controlling needs to be given to families with insufficient income and knowledge, to achieve economic prosperity for Muslim families. The purpose of this research is to find out the understanding of family household management, to find out the application of management to budgeting, to find out the obstacles in implementing family financial management, and to see whether there is an influence of internalization on the financial management of fishing families in koala villages, whose income depends on the catch they catch. influenced by natural conditions, especially wind, waves and ocean currents. This form of research uses descriptive research with a qualitative approach. Research using descriptive methods is directed at providing symptoms, facts, or events accurately and systematically regarding the characteristics of specific populations and areas. The research results show that the family's understanding of management is elementary. There is no implementation of management in family budgeting. The obstacles that occur are uncertain income and low educational knowledge. There is no influence of internalization on family financial management. Keywords:Islamic Management, Family Household, Financial Knowledge